Reccurent infections and asthma and allergic diseases in children - Bręborowicz, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
The relationships between recurrent infections, asthma and allergic diseases have been analyzed for many years. Suggestions for practice seem important and expected. Quite often it is not easy to differentiate an allergic reaction and infection, especially in the case of viral infection with mild symptoms. Sometimes both pathologies are completely independent. The main discussion focuses on the role of infection in the development of diseases and its role as a triggering factor of asthma exacerbation. For many years the concept of promotion of asthma and allergy in the course of viral infection has dominated and has been supported by epidemiological observations, and clinical and experimental studies as well. In the late 1980s a new hypothesis was proposed named the “hygiene hypothesis” of asthma/allergy. It assumes that infections (not only viral) may protect against allergic diseases. During the last 20 years many arguments have been collected for and against this hypothesis. Probably there are many confounding factors that modify the potential protective effect. However, as yet there are no recommendations for practice which could be reliable. The influence of viral infection on asthma exacerbation is well proved at different levels: epidemiology as well as clinical and experimental studies. Therapeutic intervention aimed at attenuating the course of disease in such cases is needed.